The socioeconomic burden of coronary heart disease in Korea - Chang, Hoo-Sun; Kim, Han-Joong; Nam, Chung-Mo; Lim, Seung-Ji; Jang, Young-Hwa; Kim, Sera; Kang, Hye-Young (Journal of preventive medicine and public health, 2012)
We aimed to estimate the annual socioeconomic burden of coronary heart disease (CHD) in Korea in 2005, using the National Health Insurance (NHI) claims data. A prevalence-based, top-down, cost-of-treatment method was used to assess the direct and indirect costs of CHD (International Classification of Diseases, 10th revision codes of I20-I25), angina pectoris (I20), and myocardial infarction (MI, I21-I23) from a societal perspective. Estimated national spending on CHD in 2005 was $2.52 billion. The majority of the spending was attributable to medical costs (53.3%), followed by productivity loss due to morbidity and premature death (33.6%), transportation (8.1%), and informal caregiver costs (4.9%). While medical cost was the predominant cost attribute in treating angina (74.3% of the total cost), premature death was the largest cost attribute for patients with MI (66.9%). Annual per-capita cost of treating MI, excluding premature death cost, was $3183, which is about 2 times higher than the cost for angina ($1556). The total insurance-covered medical cost ($1.13 billion) of CHD accounted for approximately 6.02% of the total annual NHI expenditure. These findings suggest that the current burden of CHD on society is tremendous and that more effective prevention strategies are required in Korea.